Mass Media Exposure of the P.G. Students in North-Eastern Hill University of Meghalaya - Daya Ram , R. Tasri Marak and M.K. Sing, (Indian Journal of Extension Education, 2017)
The study was conducted in North-Eastern Hill University (NEHU), Tura campus, and West Garo Hills district ofMeghalaya during the year 2011-2012.Total of the 165 respondents were selected for the present study. Collected datawere tabulated, organized and analyzed for drawing results by using percentage, mean, standard deviation and correlationco-efficient. Majority (70.30%) of the PG students belonged to middle age (between 22-25 years) group. 43.03 per cent ofthe PG students had undergone Certificate course in computer. Majority of the PG students (64.85%) were found to haveurban background and 35.15 per cent of them had rural background. 82.42 per cent of the PG students had medium level ofaspiration followed by high (16.98 %)and only 0.60 per cent of the PG students had low level of aspiration. Majority(47.88%) of the PG students' fathers were graduate. 46.67 per cent of the PG students mothers had high school education.It was found that majority (84.24%) of the PG students belonged to nuclear family and only 15.76% per cent of the PGstudents belonged to joint family. It could be inferred that majority (64.24%) of the PG students had medium family size. Ithas been observed that computer education, background, social participation, level of aspiration, father's occupation andtype of family were positively and significantly correlated to the mass media exposure of the PG students at 0.01 level ofprobability. These five characteristics may be termed as good predictors of mass media exposure of the PG students. The2 R value (0.759) indicated that all the eleven independent variables jointly contributed 75.9 per cent towards the variationsin mass media exposure. The F-value (43.889) was also found to be significant at 0.01 level of probability. On the basis ofthe study conducted, it could be concluded that majority of the students had medium mass media exposure computereducations, background, social participation, level of aspiration and fathers' occupation were the important factors whichhave contributed to the mass media exposure of the NEHU students.